Weaving the history of the Institute Federal Catarinense, campus Concórdia (1965-1975): stories of (in)discipline (Research, Society and Development, 2020)
The present work is an ongoing research, which aims to build the narrative of the institutional school history of the Federal Institute of Santa Catarina (IFC) Campus Concórdia, through the eyes of (in) discipline, with the time span from 1965 to 1975. The research, from a methodological point of view, is of a qualitative approach and uses mesoanalysis for the historical reading of the school institution. Mesoanalysis questions how the undisciplinary acts committed by students, corroborate, or not, with the agricultural school model, conceived in the period in question. In this work, the intention is to present one of the stages of the research in progress, namely the theoretical and methodological construction, as well as initial results. This stage is presented as fundamental in the reading and construction of the institution's history. In addition to providing a reflection on the part of teachers and students, regarding school (in) discipline.